2016
DOI: 10.1007/s00449-016-1615-8
|View full text |Cite
|
Sign up to set email alerts
|

Controlling filamentous fungi morphology with microparticles to enhanced β-mannanase production

Abstract: β-mannanase was produced mainly by Aspergillus species and can degrade the β-1,4-mannose linkages of galactomannans. This study was undertaken to enhance mannanase production using talcum and aluminum oxide as the microparticles, which control cell morphology of recombinant Aspergillus sojae in glucose and carob extract medium. Both microparticles improved fungal growth in glucose and carob pod extract medium. Aluminum oxide (1 g/L) was the best agent for glucose medium which resulted in 514.0 U/ml. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 25 publications
0
65
0
Order By: Relevance
“…When talcum microparticles were inserted into the glucose‐ and carob extract‐based media, the enzyme activity was negatively affected in the glucose‐based media and the maximum activity was 199.3 U/mL with control fermentation (no‐added talcum) while it was reached to maximum (568.7 U/mL) by adding 5 g/L of talcum in carob extract‐based media (which was 1.83‐fold higher than control fermentation). Besides, when aluminum oxide as microparticle was used in the glucose‐ and carob extract‐based media, the enzyme activity increased to 514.0 U/mL and 343.6 U/mL by the addition of 1 g/L of aluminum oxide for both media, respectively, which was 2.58‐ and 1.11‐fold higher than control fermentation . In conclusion, higher β‐mannanase fermentation results were achieved under the optimized fermentation conditions (10°Bx initial sugar concentration, 0.75% (w/v) whey concentration as an organic nitrogen source, and 8% (v/v) inoculum size) when compared with the existing results in the literature.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…When talcum microparticles were inserted into the glucose‐ and carob extract‐based media, the enzyme activity was negatively affected in the glucose‐based media and the maximum activity was 199.3 U/mL with control fermentation (no‐added talcum) while it was reached to maximum (568.7 U/mL) by adding 5 g/L of talcum in carob extract‐based media (which was 1.83‐fold higher than control fermentation). Besides, when aluminum oxide as microparticle was used in the glucose‐ and carob extract‐based media, the enzyme activity increased to 514.0 U/mL and 343.6 U/mL by the addition of 1 g/L of aluminum oxide for both media, respectively, which was 2.58‐ and 1.11‐fold higher than control fermentation . In conclusion, higher β‐mannanase fermentation results were achieved under the optimized fermentation conditions (10°Bx initial sugar concentration, 0.75% (w/v) whey concentration as an organic nitrogen source, and 8% (v/v) inoculum size) when compared with the existing results in the literature.…”
Section: Resultsmentioning
confidence: 78%
“…On the other hand, the effects of different nitrogen sources (pure nitrogen sources: yeast extract, beef extract, and ammonium nitrate; animal by‐products: meat bone meal, feather meal, and fish meal; and vegetable by‐products: red lentil, cotton seed meal, maize zein, and soybean meal) on β‐mannanase fermentation were also examined by Yatmaz et al, who reported that the highest β‐mannanase activities were found to be 695.6 U/mL with 0.5% of ammonium nitrate that is a pure nitrogen source, 597.31 U/mL with 0.75% of meat bone meal that is an animal by‐product, and 525.93 U/mL with 0.75% of soybean meal that is a vegetable nitrogen source . As a different study, β‐mannanase fermentations in glucose‐ and carob extract‐based media were performed by adding talcum and aluminum oxide microparticles into the fermentation medium to control the fungal morphology . When talcum microparticles were inserted into the glucose‐ and carob extract‐based media, the enzyme activity was negatively affected in the glucose‐based media and the maximum activity was 199.3 U/mL with control fermentation (no‐added talcum) while it was reached to maximum (568.7 U/mL) by adding 5 g/L of talcum in carob extract‐based media (which was 1.83‐fold higher than control fermentation).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,30,31 Besides, total protein analysis was carried out with ThermoScientific Coomassie (Bradford) Protein Assay Kit using bovine serum albumin solution (2 mg/ml) as a standard to determine specific inulinase and specific invertase-type activities. One unit of the enzyme activity (1 U = 16.7 nanokatal) was defined as the amount of that releases the reducing sugar equal to 1 μMe of β-D-fructose from inulin or sucrose (2%, wt/vol) in Na-acetate buffer (100 mM) at pH 4.8 and 60 C per min.…”
Section: Sugar Analysismentioning
confidence: 99%